Downregulation of sorting nexin 10 is associated with overexpression of miR-30d during liver cancer progression in rats - Nancy Cervantes-Anaya; Alberto Ponciano-Gómez; Guadalupe Soledad López-Álvarez; Christian Gonzalez-Reyes; Sergio Hernández-Garcia; María Asunción Cabañas-Cortes; José Efraín Garrido-Guerrero; Saúl Villa-Treviño (Tumor Biology)
As of 2012, liver cancer was the second leading cause of death worldwide, and hepatocellular carcinoma is the most common primary cancer of the liver. The identification of molecules that might be molecular markers or therapeutic targets is urgently needed to improve clinical management. Based on a microarray analysis performed in our laboratory, we selected six genes—namely, ANXA2, DYNLT1, PFKP, PLA2G7, KRT19 , and SNX10 —as candidates for validation as tumor markers of liver cancer in a rat model. Their patterns of overexpression in preneoplastic lesions and established tumors at 10 different time points between 24 h and 18 months were analyzed to identify putative tumor markers for further studies. We validated the microarray results by quantitative reverse transcription polymerase chain reaction, which revealed high transcriptional expression for five of the genes, consistent with their high protein expression during cancer progression reported in the literature. However, studies of the association of sorting nexin 10 with different types of cancer are limited, prompting further study. The characterization of sorting nexin 10 in preneoplastic lesions and established tumors revealed messenger RNA overexpression and a simultaneous decrease in sorting nexin 10 protein expression. A group of microRNAs related to sorting nexin 10 messenger RNA were selected based on a data analysis conducted using miRDB and microrna.org . An analysis of the expression of these microRNAs revealed an increase in the transcription of microRNA-30d whenever the sorting nexin 10 protein was downregulated. These results suggest that sorting nexin 10 is a potential liver cancer marker exhibiting characteristics of a putative suppressor protein that is likely regulated by microRNA-30d.